Bangladesh Development Update, October 2015 : On a Stable Path - World Bank (Dhaka, Bangladesh, 2015)
Progress on reducing extreme poverty and boosting shared prosperity need to be further enhanced in the near-term by sustaining Gross Domestic Product (GDP) and remittances growth, creating jobs, containing inflation, and making progress on improving the quality of public service delivery. Private investments need to increase significantly to achieve the government’s 7 percent growth target for FY16. Moving forward in the immediate future, stronger attention is needed to (i) achieve safety and labor rights compliance in the garment industry, (ii) complete the critical ongoing road, electricity and gas development projects, (iii) implement the Public Private Partnership (PPP) law, (iv) improve the efficiency and solvency of the banking sector through better banking supervision and oversight by the Bangladesh Bank and corporate governance reforms in public banks, and (v) provide access to serviced land to domestic and foreign investors through the Special Economic Zones (SEZs) initiative.